Nanoparticle-filled capillary electrophoresis for the separation of long DNA molecules in the presence of hydrodynamic and electrokinetic forces - Tseng, Wei-Lung; Huang, Ming-Feng; Huang, Yu-Fen; Chang, Huan-Tsung (Electrophoresis, 2005)
We report the analysis of long DNA molecules by nanoparticle‐filled capillary electrophoresis (NFCE) under the influences of hydrodynamic and electrokinetic forces. The gold nanoparticle (GNP)/polymer composites (GNPPs) prepared from GNPs and poly(ethylene oxide) were filled in a capillary to act as separation matrices for DNA separation. The separations of λ‐DNA (0.12–23.1 kbp) and high‐molecular‐weight DNA markers (8.27–48.5 kbp) by NFCE, under an electric field of —140 V/cm and a hydrodynamic flow velocity of 554 μm/s, were accomplished within 5 min. To further investigate the separation mechanism, the migration of λ‐DNA was monitored in real time using a charge‐coupled device (CCD) imaging system. The GNPPs provide greater retardation than do conventional polymer media when they are encountered during the electrophoretic process. The presence of interactions between the GNPPs and the DNA molecules is further supported by the fluorescence quenching of prelabeled λ‐DNA, which occurs through an energy transfer mechanism. Based on the results presented in this study, we suggest that the electric field, hydrodynamic flow, and GNPP concentration are the three main determinants of DNA separation in NFCE.